PENERAPAN METODE NETWORK FORENSIK UNTUK ANALISIS SERANGAN DOS PADA PERANGKAT ROUTER - Singgih Mitro S; Dandan Sukma (Politeknik Harapan Bersama Tegal, 2023)
Abstract Digital forensics is a part of forensic science that covers the discovery and investigation of matter (data) found on digital devices. At present the use of computer technology is so rapid that it helps human activities with the sophistication of computer network technology, behind all of that problems arise regarding network forensics. The main cause of network forensic problems is the act of misuse of technology by irresponsible people with the aim of utilizing other parties' network facilities for personal or group interests. DoS attacks (Denial of Service) one of the most common attacks on computer networks is a type of network attack Router that cannot service user requests, and ultimately causes the computer network to be down. Kata Kunci − Digital Forensics, Network Forensics, DoS